Relationship between adverse childhood experiences and Alzheimer's disease: a systematic review and meta-analysis protocol. Issue 8 (5th August 2021) - Corney, Kayla B; Pasco, Julie A; Stuart, Amanda L; West, Emma C; Quirk, Shae E; Azimi Manavi, Behnaz; Williams, Lana J
Abstract : Introduction: Alzheimer's disease has a high prevalence and a substantial impact on society, as well as the individual. Findings from clinical studies to date, suggest that multiple factors are likely to contribute to the variability seen in the progression of Alzheimer's disease. However, despite this accumulating evidence, current identified factors do not explain the full extent of disease onset. Thus, the role of additional factors needs to be explored further. One such factor is exposure to adverse childhood experiences. However, the degree of this association is unknown. This systematic review will examine the literature investigating the associations between adverse childhood experiences and the risk of Alzheimer's disease. Methods and analysis: Articles investigating associations between exposure to adverse childhood experiences and the risk of Alzheimer's disease will be identified systematically by searching CINAHL, MEDLINE and PsycInfo using Ebscohost. No restrictions on date of publication will be applied. The search strategy will be built combining the main key elements of the Population, Exposure, Comparator, and Outcomes inclusion criteria. A meta-analysis is planned and statistical methods will be used to identify and control for heterogeneity, if possible. The development of this protocol was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. Ethics and dissemination: Only published data will be used for this study, thus, ethical approval will not be required. Findings of the review will be published in a peer-reviewed scientific journal, and presented at national and international conferences. PROSPERO registration number: CRD42020191439.